Insulin Resistance and Glucose and Lipid Concentrations in a Cohort of Perinatally HIV-Infected Latin American Children - Hazra, Rohan (2013)
We measured glucose, insulin, and lipids in 249 perinatally HIV-infected Latin American children. Only one subject had impaired fasting glucose; 6.8% had insulin resistance. Abnormalities in total, LDL and HDL cholesterol, and triglycerides were reported for 13%, 13%, 21%, and 34%, respectively. Continued follow up of this populationis necessary to characterize the evolution and clinical consequences of these findings.